Glacier area stability in the Central Karakoram National Park (Pakistan) in 2001–2010: The "Karakoram Anomaly" in the spotlight. (October 2016) - Minora, Umberto; Bocchiola, Daniele; D'Agata, Carlo; Maragno, Davide; Mayer, Christoph; Lambrecht, Astrid; Vuillermoz, Elisa; Senese, Antonella; Compostella, Chiara; Smiraglia, Claudio; Diolaiuti, Guglielmina A.
The Karakoram Range is one of the most glacierized mountain regions in the world, and glaciers there are an important water resource for Pakistan. The attention paid to this area is increasing because its glaciers remained rather stable in the early twenty-first century, in contrast to the general glacier retreat observed worldwide on average. This condition is also known as "Karakoram Anomaly". Here we focus on the recent evolution of glaciers within the Central Karakoram National Park (CKNP, area: *13, 000 km 2 ) to assess their status in this region with respect to the described anomaly. A glacier inventory was produced for the years 2001 and 2010, using Landsat images. In total, 711 ice-bodies were detected and digitized, covering an area of 4605.9 ± 86.1 km 2 in 2001 and 4606.3 ± 183.7 km 2 in 2010, with abundant supraglacial debris cover. The difference between the area values of 2001 and 2010 is not significant (+0.4 ± 202.9 km 2 ), confirming the anomalous behavior of glaciers in this region. The causes of such an anomaly may be various. The increase of snow cover areas from 2001 to 2011 detected using MODIS snow data; the reduction of mean summer temperatures; and the augmented snowfall events during 1980–2009 observed at meteorological stations and confirmed by the available literature, are climatic factors associated with positive mass balances. Because the response of glacier area change to climate variation is very slow for large glaciers, the presence of some of the largest glaciers of the Karakoram Range in this region might have delayed observed effects of such climate change so far, or alternatively, the change may not be sufficient to drive an actual area increase. In this context, improved understanding the role of debris cover, meltwater ponds, and exposed ice cliffs on debris-covered glaciers, and surging glaciers (which are also found abundant here), are required is still an issue to clarify the mechanisms behind the Karakoram Anomaly.